Justice for the Environment: Developing a Set of Indicators of Environmental Justice for Scotland. (1st November 2005) - Todd, Helen; Zografos, Christos
This paper explores the context of environmental justice (EJ) in Scotland, and presents a case study whereby the main attributes for an indicator of EJ were identified, encompassing procedural and distributive aspects of justice. Through a participatory process, weights were assigned using a Multi-Criteria Analysis tool, the Analytical Hierarchy Process (AHP). Results show that overall, environmental injustices are mostly associated by respondents to unequal distribution of health burdens due to pollution, yet greater weight is attached to procedural justice by community environmental activists. The paper suggests that AHP may be applied to many situations and could form a basis for the development of tools to address and deliver EJ in Scotland.